Tunable Q-switched ytterbium-doped fibre laser with Nickel Oxide saturable absorber - Ahmad, H.; Monajemi, H.; Samion, M. Z.; Ismail, M. F.; Thambiratnam, K. (Indian journal of physics, 2021)
A passively Q-switched ytterbium-doped fibre laser (YDFL) using a nickel oxide-based saturable absorber is proposed and demonstrated. The Q-switched YDFL is capable of generating a stable output with a minimum pulse width of 6.9 µs and maximum repetition rate of 57.01 kHz. The generated pulses are highly stable, with an observed signal-to-noise ratio of ~ 33 dB. The output of the laser can be tuned over a wavelength range of 18 nm from 1035 to 1053 nm. The Q-switched YDFL would find use in multiple applications ranging from medicine to manufacturing.